Use of a decoy peptide to purify p21 activated kinase-1 in cardiac muscle and identification of ceramide-related activation - Yunbo Ke (Dove Medical Press, 2008)
Yunbo Ke, R John SolaroDepartment of Physiology and Biophysics, Center for Cardiovascular Research, University of Illinois at Chicago, Chicago, IL, USAAbstract: The p21 activated kinase-1 (Pak1) is a serine-threonine protein kinase directly activated by Cdc42 and Rac1. In cardiac myocytes, Pak1 activation leads to dephosphorylation of cTnI and C-protein through upregulation of phosphatase-2A (PP2A). Pak1 activity is directly correlated with its autophosphorylation, which occurs upon binding to the small GTPases and to some small organic molecules as well. In this report, we describe a novel method for rapid purification of endogenous Pak1 from bovine ventricle muscle. The method is simple and easy to carry out. The purified Pak1 demonstrated autophosphorylation in vitro that was enhanced by D-erythro-sphingosine-1, N-acetyl-D-erythro-sphingosine (C2-ceramide), and N-hexanoyl-D-erythro-sphingosine (C6-ceramide). Dihydro-L-threo-sphingosine (saphingol) also had some effect on Pak1 autophosphorylation. The method we developed provides a useful tool to study Pak1 activity and regulation in the heart. Moreover, our results indicate a potential role of the sphingolipids as unique signaling molecules inducing a direct activation of Pak1 that may modulate different cardiac functions.Keywords: pak1, heart muscle, purification, C2 ceramide, C6 ceramide